Use of herbal products and dietary supplements and its perception among people during the COVID-19 pandemic - Acharya, Anna; Vaidya Shrestha, Marina; Bhattarai, Ashish Kumar (Journal of Kathmandu Medical College, 2021)
Background: In Nepal herbal medicines are popular and are used along with or instead of allopathic medicines. Scarcity of efficient and new pharmacological treatment and vaccine for COVID-19 has made people find alternative ways to prevent or treat the disease, including measures like use of herbal products. Evidence-based use of herbal products should be implemented to ensure patient safety.Objectives: To determine the prevalence of use of herbal products during COVID-19 and to find patients perception regarding their use.Methods: A descriptive online cross-sectional study was conducted among adult Nepali population from 5th February to 6th June 2021 after ethical clearance at Kathmandu Medical College. Convenience sampling was used to request 292 adults who could be traced through social media, living in Nepal, one member from one household were included. Participants unable to respond to English were excluded. Questionnaires consisting of socio-demographic characteristics, use of herbal products, Likert scale to measure perception was used. Data were transferred into Excel sheet and exported to SPSS v.20 for analysis.Results: Prevalence of use of herbal products during COVID-19 was 206 (70.5%). Most common used products were Lime, Turmeric, Ginger, Honey, and Garlic. Of all, 95 (32.5%) respondents indicated that they preferred herbal products over prescription medicine for prevention and treatment of COVID-19.Conclusion: The prevalence of use of herbal products was high during the COVID-19 pandemic and almost half of the participants had perception that compared to prescription medicines herbal products were safer, had less adverse effects and were of better quality.